1997
DOI: 10.1042/cs0930541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Intake on Organ Injuries in Normotensive and Hypertensive Human Subjects

Abstract: 1. This cross-sectional study examined the influence of alcohol intake on organ injuries in normotensive and hypertensive subjects. 2. A total of 514 normotensive subjects and 302 never-treated hypertensive subjects were screened from 4557 men who entered the health check programme of our institute during the period 1990 to 1994. According to the daily alcohol consumption data reported by a self-administered questionnaire, the normotensive and hypertensive subjects were both classified into four categories; ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Moreover, earlier studies have shown dose-dependent increases in serum y-GTP and blood pressure in subjects whose daily ethanol consumption was 30 ml or more (34,35). We have previously reported that higher alcohol intake was associated with higher incidence of left ventricular hypertrophy (34), and we also have observed that fundoscopic lesions and urinary albumin excretion were increased in obese subjects (36). In the present study left ventricular hypertrophy was also correlated with serum creatinine.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, earlier studies have shown dose-dependent increases in serum y-GTP and blood pressure in subjects whose daily ethanol consumption was 30 ml or more (34,35). We have previously reported that higher alcohol intake was associated with higher incidence of left ventricular hypertrophy (34), and we also have observed that fundoscopic lesions and urinary albumin excretion were increased in obese subjects (36). In the present study left ventricular hypertrophy was also correlated with serum creatinine.…”
Section: Discussionsupporting
confidence: 63%
“…Alcohol is not only bad for blood pressure, but chronic heavy consumption and binge drinking at least are also unequivocally bad for ischaemic and haemorrhagic stroke and coronary artery disease outcomes. In addition, heavy drinking increases the risk for left ventricular hypertrophy 58 and increased arterial stiffness, 59 increases the risk of heart failure both with and without associated coronary artery disease, 60 increases the risk of atrial fibrillation 61 and increases the risk for central adiposity, 62 type 2 diabetes mellitus 63 and the metabolic syndrome 29 . Although hypertensive subjects may anticipate a decrease in risk with light drinking, any benefits have probably been overestimated because of unmeasured confounders, reverse causation and failure to account for pattern of drinking or variation in alcohol intake over time.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol-related hypertension may also be related to the consistent observation of an association of increasing alcohol intake with either left ventricular mass [110,111] or electrocardiographic evidence of left ventricular hypertrophy [112], although in each of these studies, such associations were still present after controlling for level of blood pressure. The nal target organ of interest is the kidney, with several reports that alcohol increases the risk of microalbuminuria [111,113], an effect which in one of these studies appeared to be mediated by alcoholrelated increases in blood pressure [111].…”
Section: Alcohol and Hypertensionmentioning
confidence: 96%